Update on rupatadine in the management of allergic disorders. (January 2015) - Mullol, J.; Bousquet, J.; Bachert, C.; Canonica, G. W.; Giménez‐Arnau, A.; Kowalski, M. L.; Simons, F. E. R.; Maurer, M.; Ryan, D.; Scadding, G.
Abstract: In a review of rupatadine published in 2008, the primary focus was on its role as an antihistamine, with a thorough evaluation of its pharmacology and interaction with histamine H1 ‐receptors. At the time, however, evidence was already emerging of a broader mechanism of action for rupatadine involving other mediators implicated in the inflammatory cascade. Over the past few years, the role of platelet‐activating factor (PAF) as a potent mediator involved in the hypersensitivity‐type allergic reaction has gained greater recognition. Rupatadine has dual affinity for histamine H1 ‐receptors and PAF receptors. In view of the Allergic Rhinitis and its Impact on Asthma group's call for oral antihistamines to exhibit additive anti‐allergic/anti‐inflammatory properties, further exploration of rupatadine's anti‐PAF effects was a logical step forward. New studies have demonstrated that rupatadine inhibits PAF effects in nasal airways and produces a greater reduction in nasal symptoms than levocetirizine. A meta‐analysis involving more than 2500 patients has consolidated the clinical evidence for rupatadine in allergic rhinoconjunctivitis in adults and children (level of evidence Ia, recommendation A). Other recent advances include observational studies of rupatadine in everyday clinical practice situations and approval of a new formulation (1 mg/ml oral solution) for use in children. In this reappraisal, we revisit some key properties and pivotal clinical studies of rupatadine and examine new clinical data in more detail including studies that measured health‐related quality of life and studies that investigated the efficacy and safety of rupatadine in other indications such as acquired cold urticaria, mosquito bite allergy and mastocytosis.